A guide to HPLC method validation: Take your analysis to the next level / Dr Hannis Fadzillah Mohsin - Mohsin, Hannis Fadzillah (Faculty of Pharmacy, 2023)
Analytical Unit Faculty of Pharmacy UiTM Puncak Alam has organized a two-hour webinar entitled A Guide to HPLC Method Validation: Taking Your Analysis to the Next Level on July 20, 2023. The webinar was attended by 24 participants from various groups, including both local and international (Australia and Philippines) attendees comprising postgraduate students, academicians, and researchers. High-performance liquid chromatography (HPLC) is a fundamental technique in the field of analytical chemistry, playing a crucial role in industries such as pharmaceuticals, food and beverages, environmental sciences, and more. This webinar aimed to shed light on the principles, techniques, and best practices of method validation, enabling attendees to elevate their analytical capabilities and ensure compliance with the standards. The importance of aligning method validation procedures with international standards was emphasized, ensuring accuracy, reproducibility, and compliance. The session commenced with an overview of the importance of method validation in HPLC analysis followed by the second segment, which delved into the key parameters involved in method validation, including accuracy, precision, specificity, linearity, and robustness.